SAT0253 Evans Syndrome at Childhood-Onset Systemic Lupus Erythematosus Diagnosis: A Large Multicenter Study. (15th July 2016) - Lube, G.E.; Ferriani, M.P.L.; Campos, L.M.; Terreri, M.T.; Bonfá, E.; Magalhães, C.S.; Aikawa, N.E.; Piotto, D.P.; Peracchi, O.A.; Santos, M.C.; Appenzeller, S.; Ferriani, V.P.; et al.
Abstract : Background: Evans syndrome (ES) is an uncommon manifestation characterized by autoimmune destruction of red cells and platelets and concomitant or sequential appearance of immune thrombocytopenia (ITP) and autoimmune hemolytic anemia (AIHA). This involvement has been associated to severe disease activity in adult patients with systemic lupus erythematosus (SLE), particularly at disease onset. However, ES studies in childhood-onset SLE (cSLE) patients have been rarely reported and limited to small populations. Objectives: The objective of the present multicenter study was to assess ES in a large cSLE cohort at diagnosis evaluating prevalence, clinical features, laboratory findings and outcomes. Methods: A retrospective multicenter cohort study (Brazilian cSLE group) was performed in 10 Pediatric Rheumatology services including 850 patients with cSLE (ACR criteria). None of them had secondary etiologies of autoimmune cytopenias, such as infections, primary immunodeficiencies and malignancies. Patients were divided in two groups for the assessment of lupus manifestations, laboratory exams and treatment at cSLE diagnosis: patients with ES and patients without ES. Results: ES was observed in 11/850 (1.3%) cSLE patients at diagnosis. The majority of them had hemorrhagic manifestations (58%) and active disease (82%). All patients with ES were hospitalized and none of them died. Comparisons of cSLE patients with and without ES at diagnosis revealed similar frequencies of female gender, multi-organ involvement, autoantibody profile and low complement levels (p>0.05). Patients with ES had a lower frequency of malar rash (9% vs. 53%, p=0.003) and musculoskeletal involvement (18% vs. 69%, p=0.001) than those without this complication. The median of hemoglobin [7.4 (5.4–9.4) vs. 10.3 (3.5–16.4)g/dL, p<0.001] and platelets [27 (15–54) vs. 231 (2–761)x10 3 /mm 3, p=0.005] were significantly lower in ES compared to non-ES patients, whereas lymphocytes were significantly higher in ES patients [1.8 (1–2.38) vs. 1.16 (0.07–7)x10 3 /mm 3, p<0.001]. The frequencies of intravenous methylprednisolone (82% vs. 43%, p=0.013) and intravenous immunoglobulin use (64% vs. 3%, p<0.0001) were significantly higher in the former group. Current prednisone dose between the two groups was similar [1.1 (0.76–1.5) vs. 1.0 mg/kg/day (0–30), 0.195]. Conclusions: Our large multicenter study identified that ES was a rare and severe cSLE manifestation with a difficult diagnosis due to the absence of typical lupus manifestations, often requiring hospitalization and intravenous treatment. Disclosure of Interest: G. Lube: None declared, M. Ferriani: None declared, L. Campos: None declared, M. Terreri: None declared, E. Bonfá: None declared, C. Magalhães: None declared, N. Aikawa: None declared, D. Piotto: None declared, O. Peracchi: None declared, M. C. Santos: None declared, S. Appenzeller: None declared, V. Ferriani: None declared, R. Pereira: None declared, C. Silva Grant/research support from: Conselho Nacional de Desenvolvimento Científico e Tecnolόgico (CNPq 302724/2011–7 to CAS), Federico Foundation (to CAS) and by Núcleo de Apoio à Pesquisa "Saúde da Criança e do Adolescente" da USP (NAP-CriAd) to CAS